JALI (COIX LACRYMA-JOBI L.; POACEAE) UNTUK DIVERSIFIKASI PANGAN: PRODUKTIVITAS PADA BERBAGAI TARAF PEMUPUKAN - Juhaeti, Titi (Research Center for Biology-Indonesian Institute of Sciences, 2015)
Jali (Coix lacryma-jobi L.; Poaceae) is a potential cereal for food diversification especially as carbohydrate source. The aim of this current research was to study the productivity of jali cultivated under various doses of fertilizer. Jali were planted on polybag (30x40 cm) with mix-ture of soil:compost=2:1 as planting media. Fertilizer treatments were A) 0-0-0; B) 2-1-1; C) 2,5-1,5-1,5; D) 3-2-2-; E) 3,5-2,5-2,5 and F) 4-3-3 gram urea:SP36:KCl (gr/polybag). The experiment used randomized block design with 9 replications. Result indicated that on 13 WAP (Week After Planting) the highest plant height achieved on 2,5-1,5-1,5 treatment (198,44 cm), leaf number on 4-3-3 treatment (65,44), tiller number on 4-3-3- treatment (4,22), and branch number on 2,5-1,5-1,5 treatment (5,89). These measurements were significantly different from control but not with the other fertilization treatments. On harvesting time of 6 MAP ( Months After Planting) the highest number of seed/plant was from treatment 4-3-3 (792,6) followed by treatment 2-1-1 treatment (672,5). The result of this study suggested that 2-1-1 gram Urea:SP36:KCl (gr/polybag) treatment was the best in increasing hanjeli productivity.